Speaking law in plain Indonesian: measuring whether automated legal simplification improves public understanding without distorting legal meaning - Aisyah Deby Damayanti (CV Narasi Khatulistiwa Indonesia, 2026)
Background: As Indonesian citizens increasingly encounter law through digital portals, public-service notices, regulatory explanations, and automated interfaces, legal communication must become intelligible without weakening the normative precision that gives law its institutional force. Objective: This study examines whether automated plain-Indonesian simplification can improve public understanding of legal texts while preserving their legal meaning. Method: Using a paired-corpus design, this study analyses 21 excerpts from 18 verified public legal documents, comparing original legal-Indonesian passages with automated simplified versions through linguistic burden analysis, simplification-operation coding, and legal-meaning preservation assessment. Results: The findings show that legal difficulty is driven less by technical vocabulary than by embedded conditions, nominalisation, passive agency, cross-referential dependency, and dense modality. Simplification works most effectively when it sequences legal conditions, restores visible agency, explains necessary legal terms, and unpacks abstract legal processes without changing rights, duties, prohibitions, exceptions, procedures, or sanctions. Implication: However, simplification becomes legally fragile when it compresses scope, shifts institutional responsibility, weakens modal force, or omits qualifying conditions. Novelty: The novelty of this study lies in its dual evaluation model, which treats automated legal simplification as a constrained transformation requiring both accessibility gain and legal-fidelity preservation.